RELATIONSHIP BETWEEN HEMODIALYSIS AND Hb LEVELS WITH LEVEL OF FATIGUE - ifa roifah; EKA NUR SO'`EMAH; SRI SUDARSIH (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Hemodialysis is one of the interventions for patients with chronic renal failure which if done for a long time will cause fatigue symptoms as much as 82% to 90% of patients. The duration of the patient undergoing hemodialysis will increase fatigue levels; this will cause decreased concentration, malaise, sleep disturbances, emotional disturbances and reduce the ability of the patient's ability in daily activities. The exact symptom that occurs in patients with chronic renal failure is a decrease in Hb levels. The purpose of this study was to prove the long-standing relationship between hemodialysis and Hb levels with fatigue levels. The research design uses correlation analytic. The variables studied were hemodialysis duration, hemoglobin level,and fatigue level. The sample size in this study was 61 respondents with simple random sampling technique. Data analysis uses multiple linear regression. The results of the study simultaneously showed a long relationship between hemodialysis and HB levels with fatigue levels. Patients who have long undergone hemodialysis will have high levels of urea and creatinine. High urea will interfere with the production of the hormone erythropoietin. As a result of the number of red blood cells decreases, as a result, the patient will experience symptoms of fatigue.